CMHN (Community Mental Health Nursing) in Efforts to Improve Literacy and Empowerment Strategies for Posyandu Cadres Towards a Mentally Healthy Neighborhood - Wenny, Bunga Permata; Sarfika, Rika; Mahathir; Erwina, Ira; Freska, Windy; Adelirandy, Okky; Safitri, Kiki Hardiansyah; Fernandes, Feri; Refnandes, Randy; Lenggogeni, Devia Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Mental health remains a significant global challenge, including in Padang City, where community-based services are not yet fully optimized. In Ganting Village, posyandu cadres have limited capacity to conduct early detection of mental health disorders, which may hinder timely intervention. This community engagement initiative was designed to enhance mental health literacy and strengthen cadres’ competencies through the Community Mental Health Nursing (CMHN) approach. The program employed a combination of socialization, structured health education on the concept of mental well-being, hands-on training in the use of validated screening tools (PHQ-2, GAD-2, and EPDS), and field-based mentoring. Evaluation was carried out using pre- and post-tests as well as observational assessments of cadre participation was conducted on August 8, 2025.Findings revealed an increase in the average knowledge score from 6.0 to 8.0 (33% improvement). Cadres demonstrated improved soft skills in conceptual understanding and hard skills in administering screening instruments. Importantly, they were able to identify cases of postpartum depression, underscoring the practical relevance of the intervention. Overall, the program proved effective in preparing cadres as community change agents in mental health promotion. Empowering local cadres through CMHN contributes to strengthening preventive strategies and advancing Ganting Village toward a mental health–ready community.